FIRST RECORD OF SUCCESSFUL BREEDING OF THE CRITICALLY ENDANGERED WHITE-BELLIED HERON (ARDEA INSIGNIS) IN BROADLEAVED TREES - P. Khandu; G. A. Gale; R. Pradhan; I. P. Acharja; S. Bumrungsri1 (Journal of Animal and Plant Sciences, 2020)
The global population of White-bellied Heron Ardea insignis is likely in rapid decline across its native range and verging on extinction. Although studies focusing on foraging habitat preferences and feeding ecology have been conducted in the past, its nesting ecology and breeding biology are poorly understood. Moreover, earlier records indicated that the bird exclusively nests on chir pine trees in temperate forest between the altitudes of 600-1200 m. Here, we report the first record of successful breeding on broadleaved trees in Bhutan. The two nests we discovered were platforms made from dried twigs and small leafless branches on the topmost canopies of two broadleaved species Michelia champaca, and Pterospermum acerifolium in riverine forest. Five juveniles (two from one nest and three from the other) fledged from these nests which were at much lower altitudes than previously known. These findings suggest a possibility of a wider distribution of nesting habitat in the region and a need for further research and protection of this heron’s primary riverine habitat to save this bird from extinction.
Keywords: Ardea insignis; White-bellied Heron; Nesting; Broad-leaved trees; Conservation